STUDY ON DIVERSITY OF RICE FIELD BLUE-GREEN ALGAE FROM RICE FIELD OF CHAPRA IN BIHAR - Kumari, Sachi; Jha, Amrendra Kumar (The Scientific Temper, 2018)
The blue-green algae are primitive but the fortunate and sustained organism during the course of evolution. They are emerging candidates for efficient conversion of solar energy into chemical energy. The cyanophyte system in rice field produces oxygen as a by-product and agricultural practices in such fields produces biomass to decrease carbon dioxide and accomplish nitrogen fixation. The blue-green algal diversity was investigated in local rice fields through soil samples from sites having spatio-temporal differences during the study period. The study revealed 17 genera and 21 species of blue-green algae population as a major nutritive material in rice fields.